2022
DOI: 10.1101/2022.04.27.489676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Neutrophils Extracellular Traps (NETs) reduces multiple organ injury in a COVID-19 mouse model

Abstract: COVID-19 is characterized by severe acute lung injury, which is associated with neutrophils infiltration and release of neutrophil extracellular traps (NETs). COVID-19 treatment options are scarce. Previous work has shown an increase in NETs release in the lung and plasma of COVID-19 patients suggesting that drugs that prevent NETs formation or release could be potential therapeutic approaches for COVID-19 treatment. Here, we report the efficacy of NET-degrading DNase I treatment in a murine model of COVID-19.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(68 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, data from our lab also showed that treatment of Tg-infected mice with NETs-degrading DNase ameliorates lung pathology (Veras et al). Thus, we evaluated whether C5a/C5aR1 signaling would be involved in NETs formation in the lungs of SARS-CoV-2-infected Tg mice.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, data from our lab also showed that treatment of Tg-infected mice with NETs-degrading DNase ameliorates lung pathology (Veras et al). Thus, we evaluated whether C5a/C5aR1 signaling would be involved in NETs formation in the lungs of SARS-CoV-2-infected Tg mice.…”
Section: Resultsmentioning
confidence: 93%
“…As expected, an addition of exogenous DNase I to the whole blood eliminates the NETs accumulation and dramatically reduces adhesion and aggregation of platelets and leukocytes. Animal studies showed that DNase I decreases detectable plasma levels of NETs, improved clinical disease, and reduced lung, heart, and kidney injuries in SARS-CoV-2-infected K18-hACE2 mice (85). Additionally, an intravenous infusion of recombinant DNase I mitigates peribronchiolar, perivascular, and interstitial inflammation, acute respiratory distress syndrome, induced by poly [I:C](81).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Animal studies showed that DNase I decreases detectable plasma levels of NETs, improved clinical disease, and reduced lung, heart, and kidney injuries in SARS-CoV-2-infected K18-hACE2 mice. 83 Additionally, an intravenous infusion of recombinant DNase I mitigates peribronchiolar, perivascular, and interstitial inflammation, ARDS, induced by poly [I:C]. 79 A recent pilot clinical trial has also demonstrated its therapeutic efficacy of long-acting nanoparticle DNase I in COVID-19 patients, leading to reduction of plasma levels of cfDNA and neutrophil activities.…”
Section: Supplementary Video S3mentioning
confidence: 99%
“… 112 In SARS‐CoV‐2‐infected K18 mice, the treatment with subcutaneous DNase I improved clinical score of disease and reduced lung injury (Veras et al, BioRxiv). 113 In COVID‐19 patients, clinical trials are being conducted with aerosolized DNase treatment (NCT04541979) as well as DNase in combination with Baricitinib (Janus Kinase inhibitor) and Tocilizumab (anti–interleukin‐6) (NCT05279391). The combination of DNase with other drugs already used for the treatment of COVID‐19, such as dexamethasone, or Baricitinib and Tocilizumab, represents a promising multi‐pronged strategy.…”
Section: Therapeutic Approaches Targeting Neutrophilsmentioning
confidence: 99%
“…Interestingly, the disruption of NETs with inhaled recombinant DNase treatment improved lung function in cystic fibrotic (CF) mice and helped to solubilize sputum from CF patients 112 . In SARS‐CoV‐2‐infected K18 mice, the treatment with subcutaneous DNase I improved clinical score of disease and reduced lung injury (Veras et al, BioRxiv) 113 . In COVID‐19 patients, clinical trials are being conducted with aerosolized DNase treatment (NCT04541979) as well as DNase in combination with Baricitinib (Janus Kinase inhibitor) and Tocilizumab (anti–interleukin‐6) (NCT05279391).…”
Section: Therapeutic Approaches Targeting Neutrophilsmentioning
confidence: 99%